(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Brain blood vein cerebrovascular anomalies (BBVCA) of diseases in development important from factors one This is the article describes the stroke, blood to leave and ischemic to events impact studied. In the study arteriovenous malformations, aneurysms and Moya-Moya disease cerebrovascular to diseases dependency analysis made, their danger level evaluated. Magnetic resonance imaging angiography (MRA) and computer tomography such as angiography (CTA) advanced diagnostics methods efficiency seeing Also, the BBVCA early diagnosis and prevent to take measures discussion Research results these anomalies early determination and effective treatment cerebrovascular diseases development prevent to take help to give shows.